ANALYZING THE SYNERGY BETWEEN PROJECT-BASED LEARNING, ECONOMIC DYNAMICS, AND MARKETING TRIUMPH: A HOLISTIC INVESTIGATION - Iis Surgawati; Iwan Ridwan Paturochman; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2023)
This comprehensive investigation provides an in-depth analysis of the complex and symbiotic relationship between project-based learning (PBL), economic dynamics, and marketing triumph. Utilizing a thorough literature review approach, we delve into the multifaceted impacts of PBL, exploring its ability to cultivate critical thinking, collaboration, and practical application of knowledge among learners. Furthermore, we meticulously examine how economic factors intricately influence educational outcomes and market strategies, shedding light on the pervasive role of socioeconomic disparities and consumer behavior in shaping educational and business landscapes. Additionally, our study delves into the nuanced mechanisms through which marketing initiatives capitalize on economic insights to effectively drive brand loyalty and revenue growth. Through a synthesis of insights drawn from diverse academic disciplines, this research elucidates the intricate interconnectedness of PBL, economic dynamics, and marketing success. By offering actionable insights and practical recommendations, our findings aim to empower educators, policymakers, and businesses to navigate the complexities of contemporary environments with a focus on fostering innovation and sustainable growth.